Patterning of Lyotropic Chromonic Liquid Crystals by Photoalignment with Photonic Metamasks. Issue 21 (15th March 2017) - Peng, Chenhui; Guo, Yubing; Turiv, Taras; Jiang, Miao; Wei, Qi‐Huo; Lavrentovich, Oleg D.
Abstract : Controlling supramolecular self‐assembly in water‐based solutions is an important problem of interdisciplinary character that impacts the development of many functional materials and systems. Significant progress in aqueous self‐assembly and templating has been demonstrated by using lyotropic chromonic liquid crystals (LCLCs) as these materials show spontaneous orientational order caused by unidirectional stacking of plank‐like molecules into elongated aggregates. In this work, it is demonstrated that the alignment direction of chromonic assemblies can be patterned into complex spatially‐varying structures with very high micrometer‐scale precision. The approach uses photoalignment with light beams that exhibit a spatially‐varying direction of light polarization. The state of polarization is imprinted into a layer of photosensitive dye that is protected against dissolution into the LCLC by a liquid crystalline polymer layer. The demonstrated level of control over the spatial orientation of LCLC opens opportunities for engineering materials and devices for optical and biological applications. Abstract : Spatially varying, surfactant‐free, patterned alignment of lyotropic chromonic liquid crystals (LCLCs) is demonstrated. The approach is based on photonic metamasks with a pattern of nanoslits that control the polarization of transmitted light. The aligning agent represents an azo dye with an additional layer of photopolymerizable mesogenic monomer that separates the dye from the LCLC while transfering the alignment pattern.